1998
DOI: 10.2169/internalmedicine.37.1064
|View full text |Cite
|
Sign up to set email alerts
|

Kimura's Disease Associated with Bronchial Asthma Presenting Eosinophilia and Hyperimmunoglobulinemia E which were Attenuated by Suplatast Tosilate (IPD-1151T).

Abstract: A 29-year-old man developed atopic bronchial asthma in association with eosinophilia and hyperimmunoglobulinemia E (hyper-IgE). A biopsy specimen from an inguinal lymph node showed changes consistent with Kimura's disease. IPD-1151T (suplatast tosilate), an anti-allergy drug, attenuated eosinophilia and hyper-IgE as well as the serum level ofeosinophil cationic protein (ECP). The drug, however, did not affect the positivity for specific IgE antibodies against common allergens or the bronchial hyperresponsivene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 10 publications
0
15
0
Order By: Relevance
“…First, the association of peripheral eosinophilia and nephrotic syndrome (12,13) has been frequently discussed in Kimura's disease. Second, many different regional lymph nodes (14) or extremities (15) involvement at presentation have been reported. Third, the rate of recurrence may be as high as 257 5% after surgical excision (11,16) and 11~17% after local radiotherapy (11,17 …”
Section: F I G U R E 2 ( A) P H O T O Mi C R O G R a P H O F T H E mentioning
confidence: 99%
“…First, the association of peripheral eosinophilia and nephrotic syndrome (12,13) has been frequently discussed in Kimura's disease. Second, many different regional lymph nodes (14) or extremities (15) involvement at presentation have been reported. Third, the rate of recurrence may be as high as 257 5% after surgical excision (11,16) and 11~17% after local radiotherapy (11,17 …”
Section: F I G U R E 2 ( A) P H O T O Mi C R O G R a P H O F T H E mentioning
confidence: 99%
“…A high prevalence of nephropathy has been reported in patients with KD (8)(9)(10), and nephrotic syndrome is seen in the majority of reported cases, with most patients displaying mild histological changes on renal biopsies and many responding well to steroid therapy. The histological findings are mild to moderate, with membranous nephropathy, mini- There are some case reports of bronchial asthma occurring in association with KD (11,12), such as those described by Tsukagoshi et al (11). In their report, suplatast tosilate reduced the number of peripheral blood eosinophils and the serum levels of IgE and eosinophilic cationic proteins (ECPs), thereby improving asthma symptoms.…”
Section: Discussionmentioning
confidence: 97%
“…Complications such as nephrotic syndrome (8-10), bronchial asthma (11,12), atopic dermatitis, urticaria, ulcerative colitis (13) and aortitis syndrome (14) have been reported. In a review of 429 Japanese cases of KD, Ishii identified five cases associated with bronchial asthma, three cases associated with allergic rhinitis, two cases associated with atopic dermatitis and five cases associated with urticaria, suggesting that an allergic mechanism may contribute to KD (2).…”
Section: Discussionmentioning
confidence: 99%
“…Surgical excision, systemic corticosteroids and local radiation are often performed [7]. Treatments with immunosuppressive agents [2,23], cytotoxic therapy [24], antiallergic drugs [5,25] and all-trans-retinoic acid [26] have also been reported. Surgical resection and radiotherapy were not indicated for our case because there were multiple tumors.…”
Section: Discussionmentioning
confidence: 99%